IMPROVING DESCRIPTION TEXT WRITING SKILLS IN BUGIS USING YOUTUBE MEDIA FOR STUDENTS OF CLASS VIII SMP NEGERI 2 LILIRIAJA SOPPENG DISTRICT - Najma Aliyah; Johar Amir; Nensilianti (Media Inovasi Pendidikan dan Publikasi, 2024)
This study aims to describe the improvement of description text writing skills in Bugis language using YouTube media of students of class VIII.A SMP Negeri 2 Liliriaja. This research is a classroom action research (PTK) consisting of two cycles. Data collection techniques used in this study were observation techniques, test techniques, and documentation techniques. The data obtained were analyzed by descriptive analysis. In the learning process, teachers have utilized audio-visual media effectively so that students are more enthusiastic in participating in learning. On learning outcomes, students showed improvement by writing description text in bugis language through YouTube media. Based on the results of data analysis obtained, this was obtained after comparing the test results in cycle I and cycle II. The test results obtained were that in cycle I there was only 1 student who scored above 75, while in cycle II all students scored above 75. The increase in the average score of the test results for each cycle, namely in cycle I (62.00), cycle II (81.00). This shows that learning to write description text with audio-visual media for students of class VIII A SMP Negeri 2 Liliriaja has improved.